1990
DOI: 10.1111/j.1523-536x.1990.tb00007.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Breast Surgery, Breast Appearance, and Pregnancy‐Induced Breast Changes on lactation Sufficiency as Measured by Infant Weight Gain

Abstract: We conducted a prospective study of the associations between several biologic and surgical breast factors and the onset of lactation in 319 healthy, motivated, primiparous women who were breastfeeding term, healthy, appropriate for gestational age or large for gestational age infants. During the last trimester of pregnancy subjects' breasts were examined for surgical incisions, size, symmetry, and nipple protuberance, and women estimated their prenatal breast enlargement. At two visits in the first two weeks p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 26 publications
2
76
0
2
Order By: Relevance
“…According to this criterion, four of the subjects in the current study had minimal breast enlargement, yet the lowest infant growth rate was 25·7 g day¢ during the first month. However, our data are compatible with that of Neifert et al (1990), since they found that 75% of the women who had minimal breast increase during pregnancy did have a lactation outcome described as…”
Section: Milk Productionsupporting
confidence: 80%
“…According to this criterion, four of the subjects in the current study had minimal breast enlargement, yet the lowest infant growth rate was 25·7 g day¢ during the first month. However, our data are compatible with that of Neifert et al (1990), since they found that 75% of the women who had minimal breast increase during pregnancy did have a lactation outcome described as…”
Section: Milk Productionsupporting
confidence: 80%
“…Neifert et al followed 319 primiparous women who were motivated to breastfeed. 31 When women with prior breast surgery were excluded, 13.1% had insufficient milk production. In a secondary analysis of participants in Project Viva, 32 67 of 495 mothers (13.5%) reported early introduction of formula or weaning at less than 3 months due to problems with milk production.…”
Section: Discussionmentioning
confidence: 99%
“…10 In augmentation surgery, although some studies assert that it does not interfere with lactation, 11,12 others mention insufficient lactation and low milk production, closely related to the periareolar incision and to the compression of the glandular tissue, as a result of the implanted volume and of the placement of the prosthesis under the gland. 9,[13][14][15] Its impact is weaker than that of the breast reduction surgery because the damage to the glandular structure is smaller or nonexistent.…”
Section: Discussionmentioning
confidence: 99%